Combination of efficient charge separation with the assistance of novel dual Z-scheme system: self-assembly photocatalyst Ag@AgI/BiOI modified oxygen-doped carbon nitride nanosheet with enhanced photocatalytic performance - Liang, Chao; Niu, Cheng-Gang; Guo, Hai; Huang, Da-Wei; Wen, Xiao-Ju; Yang, Shi-Feng; Zeng, Guang-Ming (Catalysis science & technology, 2018)
Natural or artificial Z-scheme systems have been applied for tackling environment pollution and energy crisis owing to the high reduction and oxidation ability driven by the unique interface charge-pairs transfer. However, a dual Z-scheme system combining direct Z-scheme and indirect Z-scheme is seldom adopted for photocatalysis. In this study, the self-assembly photocatalyst Ag@AgI/BiOI/g-C 3 N 4 was successfully fabricated based on the dual Z-scheme system combining direct and indirect Z-scheme systems. The synergistic effect of the dual Z-scheme system towards tetracycline (TC) degradation over the hybrid composites under visible light irradiation was investigated. Compared with single Z-scheme system composites of BiOI/g-C 3 N 4 and AgI/BiOI, the as-synthesized composite of AgI/BiOI/g-C 3 N 4 exhibited superior photocatalytic performance under identical conditions. The dual Z-scheme system was verified by active species generation (˙O 2 − , ˙OH and h + ), trapping experiments and ESR analysis. Furthermore, the photostability and practical application were investigated based on a recycle experiment and controllable experiments. A possible dual Z-scheme mechanism for enhanced photocatalytic performance with ultra-fast charge-separation efficiency and high redox ability was proposed. This study will provide new insight to the design of novel heterojunction composites based on the dual Z-scheme system to deal with organic pollution and energy crisis.